Plan de mejoramiento productivo de animales menores en la parroquia Lourdes perteneciente al cantón Paltas - Robles Lara, Juan Carlos (2017)
The present research entitled "Plan of Improvement Productive of Small Animals in Lourdes Parish belonging to Canton Paltas", aimed to develop the following objectives: to carry out a situational diagnosis of minor animals of the Lourdes parish of the Paltas canton; To elaborate a plan of productive improvement of smaller animals for the zone of study; Perform a cost-benefit analysis of the production of smaller animals; And socialize the results to those interested in the subject. The methodology applied was to establish the productive characteristics of the study area, which served to elaborate the diagnosis of the farms, as well as to determine the analysis of the internal and external environment, and then finalize with the elaboration of the plan for the productive improvement of species Minors of the Lourdes parish. It should be noted that the techniques used during the research were: direct observation, and the application of the SWOT matrix. The results show the precarious management conditions that have the producers of the area, as detailed in the diagnosis of the farm, which reflects the low production of smaller species; For that reason, to increase the production of livestock, we propose the plan of productive improvement which has a duration of 5 years, where the ratio Profit / cost after performing the respective profitability analysis shows the following data: for pork production is 1, 10, so also for poultry production is 1.14 and finally for caprine production the B / C ratio is 1.66. In this way it is concluded satisfactorily, since the elaboration of the productive improvement plan allows to show to the population the benefits that can bring with the implementation of an initiative like this, requiring little investment and increasing its profitability. Finally, due to the lack of association of the community members of the Lourdes parish, it is undoubtedly recommend the implementation of social assistance projects where one of the main objectives is to form a legally consolidated association, whose work improves their quality of life and Their income. Finally there is recommended the project execution of training and social help, in order that the producers of minor animals, could grow and interact inside the dynamics of the estates of the parish Lourdes.